Impact of Commercial Protective Culture on Manouri PDO Cheese - Thomas Bintsis; Maria A. Kyritsi (Fermentation)
Manouri is a Greek whey cheese, with a Protected Denomination of Origin recognition, produced by heating the cheese whey and added milk and/or cream at high temperatures (88–90 °C) to form a coagulum. High-heat treatment results in the inactivation of any indigenous microorganisms from the raw materials. However, the high moisture, fat and pH of the cheese make it a favorable medium for the growth of any microbial contamination. The objective of this study was to investigate the application of a commercial protective culture (CPC) on the microbial profile of Manouri cheese during storage. Three treatments were prepared: S1 was the control cheese with sterile water sprayed on the surface, S2 was sprayed with a dense CPC and S3 with a diluted CPC. The experimental cheeses were covered with greaseproof paper and stored at 5 °C for 21 days. For all three treatments, the fat content and total solids showed a significant increase during storage, while protein and carbohydrates showed a significant decrease at 14 days. The application of the CPC resulted in cheeses with higher pH than the control cheese, probably due to the growth of acidifying lactic acid bacteria in the microbiota of the S2 and S3 cheeses. Manouri cheese sprayed with the CPC showed a reduction of 1.60–1.69 log CFU/g in the population of yeasts; no effect was observed on Enterobacteriaceae and Staphylococcus spp. The dominant yeast microbiota was identified as Candida zeylanoides (63.5%), Candida parapsilosis (21.1%) and Candida famata (15.4%). Although the application of the CPC was not able to control the spoilage bacteria, it showed an effective way to control the growth of yeasts in Manouri cheese. However, the presence of certain Candida spp. reveals the significance of applying good hygiene practices throughout the cheesemaking process.